Impacts of a warming climate on the non-breeding distribution of a classic differential migrant - O’Neal, Dawn M.; Austin, Suzanne H.; Ketterson, Ellen D. (Frontiers in Bird Science, 2024)
Many changes in species' geographic distributions have been attributed to recent climate warming. One understudied phenomenon is the effect of climate change on differential migrants, species in which the sexes differ in distance migrated to and from the breeding range. We evaluated the impact of climate change on differential migration in the dark-eyed junco (Junco hyemalis) by assessing temporal and geographic changes in overall population abundance throughout the winter range over the past 60 years. We also compared the abundance of females in wintering populations studied 15 years ago with historical abundances studied 45 years ago We observed a northward movement of the population as a whole and an increase in female abundance at higher latitudes that correlated with recent changes in winter climate. These findings suggest that climate change has reduced distance migrated in this species and increased the proportion of females wintering at higher latitudes, providing new insights into the impact of climate warming on migratory distance and winter distributions.